Swimming cap containing organic silicon waterproof coating and preparation method of swimming cap
By using a combination of silicone waterproof coating and modified filler on the swimming cap, the penetration and aging problems of traditional swimming caps are solved, and high water resistance, antistatic and dirt resistance are achieved, improving the swimmer's experience and Equipment quality.
Patent Information
- Application Number
- CN202411027425.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-29
- Publication Date
- 2024-12-13
AI Technical Summary
Traditional swimming caps are prone to penetration and aging problems during long-term use or under specific water quality conditions, resulting in damp hair and discomfort in scalp, affecting swimming experience and ear health, and it is difficult to ensure breathability, reduce wearing pressure and improve while maintaining waterproofing. Overall comfort.
Designed with a swim cap containing a silicone waterproof coating, the coating structure includes a base layer, a colloidal layer and a silicone waterproof coating. It improves waterproof, anti-static and dirt resistance through modified fillers and composite particle structures, and uses epoxy Block polymers and amylopectin compositions enhance mechanical and antistatic properties.
It greatly improves the waterproof, anti-static and dirt resistance of swimming caps, extends service life, improves swimmers' comfort and swimming experience, and has excellent market prospects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of swimming supplies, and in particular to a swimming cap containing a silicone waterproof coating and a preparation method thereof. Background Art
[0002] With the popularity of water sports and the development of technology, swimming enthusiasts and professional athletes have increasing requirements for swimming equipment, especially the performance requirements for swimming caps. Traditional swimming caps are mostly made of latex or polyurethane materials. Although they have certain waterproof properties, they often have problems such as penetration and aging after long-term use or under specific water conditions, resulting in damp hair, scalp discomfort, and even affecting the swimming experience and performance. In particular, water seeping into the ears not only affects the comfort during swimming, but may also cause ear health problems, such as swimmer's otitis. Therefore, the development of a swimming cap that is not only effectively waterproof, but also provides a comfortable fit and protects the ears has become an urgent need in the industry.
[0003] In recent years, silicone materials have gradually become the preferred material for high-end swim caps due to their excellent flexibility, aging resistance and good sealing performance. However, even silicone swim caps face the challenge of how to ensure breathability, reduce wearing pressure and improve overall comfort while maintaining a high degree of waterproofness. In addition, the differences in head sizes among different users require that the swim cap design must have good adaptability and adjustability.
[0004] Therefore, in order to solve the above problems, the present application provides a swimming cap with a silicone waterproof coating and a preparation method thereof. The swimming cap prepared by the present application has excellent mechanical / mechanical properties while being able to ensure good waterproof, antistatic and dirt-resistant properties, greatly improving the use quality and service life of existing swimming caps, and has very excellent market and application prospects. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a swimming cap containing a silicone waterproof coating, the structure of which includes: a base layer, a colloid layer located on the surface of the base layer, and a silicone waterproof coating located on the surface of the colloid layer.
[0006] As a preferred solution, the total thickness of the swimming cap is 0.3-0.6 mm.
[0007] As a preferred solution, the thickness of the base layer is 0.2-0.4 mm.
[0008] As a preferred solution, the thickness of the colloid layer is 0.04-0.08 mm.
[0009] As a preferred solution, the thickness of the silicone waterproof coating is 0.1-0.2 mm.
[0010] As a preferred solution, the base layer is any one of polyester, aramid, and spandex, or a blended fabric of two of them.
[0011] As a preferred solution, the base layer is polyester.
[0012] As a preferred solution, the raw materials of the colloidal layer include, by mass, 80 to 100 parts of organic polysiloxane I, 5 to 10 parts of hydrogenated polysiloxane I, 20 to 35 parts of modified resin I, 0.5 to 3 parts of catalyst, 20 to 25 parts of filler, 1 to 6 parts of dispersant, and 4 to 10 parts of flame retardant.
[0013] As a preferred solution, the organopolysiloxane I is a composition of polydimethylsiloxane and epoxy-modified polysiloxane.
[0014] As a preferred solution, the mass ratio of the polydimethylsiloxane to the epoxy-modified polysiloxane is (4-6): (1.5-2).
[0015] As a preferred solution, the mass ratio of the polydimethylsiloxane to the epoxy-modified polysiloxane is (5-5.5):(1.6-1.8).
[0016] As a preferred solution, the viscosity of the epoxy-modified polysiloxane is 1000-2500 cp, and the test temperature is 25°C.
[0017] As a preferred solution, the hydrogenated polysiloxane I is hydrogenated end-capped polydimethylsiloxane.
[0018] As a preferred solution, the hydrogen content of the hydrogenated polysiloxane I is 0.5-1 wt%.
[0019] As a preferred solution, the modified resin I is vinyl MTQ resin.
[0020] As a preferred solution, the mass ratio of the organopolysiloxane I to the modified resin I is (8.5-9.5):(2.4-2.6).
[0021] As a preferred solution, the mass ratio of the organopolysiloxane I to the modified resin I is 9:2.5.
[0022] As a preferred solution, the filler is at least one of talcum powder, white carbon black, bentonite and sericite powder.
[0023] As a preferred solution, the filler is sericite powder.
[0024] As a preferred solution, the average particle size of the sericite powder is 0.1-0.3 μm.
[0025] As a preferred solution, the dispersant is at least one of alkyl glycoside, lauryl alcohol polyoxyethylene ether, povidone, polyethylene glycol, and betaine.
[0026] As a preferred solution, the flame retardant is at least one of aluminum hydroxide, magnesium hydroxide, triphenyl phosphate, zinc borate, MCA, and MA.
[0027] As a preferred solution, the flame retardant is triphenyl phosphate.
[0028] As a preferred scheme, the raw materials of the organic silicone waterproof coating include, by mass: 100-120 parts of organic polysiloxane ⅠⅠ, 10-20 parts of hydrogenated polysiloxane ⅠⅠ, 20-35 parts of modified resin ⅠⅠ, 0.5-3 parts of cross-linking agent, 0.5-2 parts of catalyst, 20-30 parts of modified filler, 5-10 parts of surfactant, 10-15 parts of auxiliary agent, and 4-8 parts of colorant.
[0029] As a preferred solution, the organopolysiloxane II is a composition of high-viscosity vinyl polydimethylsiloxane and low-viscosity vinyl polydimethylsiloxane.
[0030] As a preferred solution, the mass ratio of the high viscosity vinyl polydimethylsiloxane to the low viscosity vinyl polydimethylsiloxane is (3.5-5):(2-2.5).
[0031] As a preferred solution, the mass ratio of the high viscosity vinyl polydimethylsiloxane to the low viscosity vinyl polydimethylsiloxane is (4-4.5):(2.4-2.5).
[0032] As a preferred solution, the viscosity of the high viscosity vinyl polydimethylsiloxane is 10000-14000 cp, and the test temperature is 25°C.
[0033] As a preferred solution, the viscosity of the low-viscosity vinyl polydimethylsiloxane is 4000-6000 cp, and the test temperature is 25°C.
[0034] As a preferred solution, the hydrogenated polysiloxane II is polymethyl hydrogen siloxane.
[0035] As a preferred solution, the hydrogen content of the polymethylhydrogensiloxane is 1.2-1.6 wt %.
[0036] As a preferred solution, the catalyst is any one of platinum catalysts.
[0037] As a preferred solution, the modified resin II is a composition of vinyl MTQ resin and methyl vinyl MQ resin.
[0038] As a preferred solution, the mass ratio of the vinyl MTQ resin to the methyl vinyl MQ resin is (1-1.5): (3.5-4).
[0039] As a preferred solution, the vinyl content of the vinyl MTQ resin is 2-3.5wt%.
[0040] As a preferred solution, the vinyl content of the methyl vinyl MQ resin is 1-1.5 wt %.
[0041] As a preferred solution, the cross-linking agent is dicumyl peroxide or benzoyl peroxide.
[0042] As a preferred solution, the preparation method of the modified filler comprises the following steps: S1: adding carbon nanotubes and zinc oxide to deionized water, heating to 60-65°C, adding succinic anhydride and silane coupling agent, stirring at 80-120 r / min for 2-3 hours, centrifuging and precipitating after completion to obtain pretreated composite particles; S2: adding deionized water to the pretreated composite particles and mixing them evenly with a methanol solution of zinc acetate, heating to 50-55°C, keeping the temperature for 30-40 minutes, and then heating to 50-55°C for 30-40 minutes. The mixture was heated to 65-70°C, and a methanol solution of dimethylimidazole was added dropwise for 1-1.5 hours. S3: After the addition was completed, the temperature was lowered to 45-50°C, and ultrasonic heating was performed at a power of 200-300W for 3-3.5 hours. After the reaction was completed, ammonia water was added to the obtained product to adjust the pH to 8.5-9.5, and then an ethanol solution of tetraethyl orthosilicate was added. The mixture was stirred at 55-60°C for 1-1.5 hours. After the reaction was completed, the product was completely precipitated in the solution, and the product solution was filtered, washed, and vacuum dried to obtain the product.
[0043] As a preferred solution, the mass ratio of the carbon nanotubes, zinc oxide, succinic anhydride and silane coupling agent is (3-3.5): (0.6-1): (1-1.2): (0.3-0.5).
[0044] As a preferred solution, the mass ratio of the pretreated composite particles, zinc acetate, dimethylimidazole and tetraethyl orthosilicate is (2-2.4): (1.6-1.8): (1-1.1): (0.4-0.5).
[0045] As a preferred solution, the mass ratio of the pretreated composite particles, zinc acetate, dimethylimidazole and tetraethyl orthosilicate is (2.2-2.4): (1.7-1.8): (1-1.1): (0.4-0.45).
[0046] As a preferred solution, the average diameter of the carbon nanotubes is 1.5-2.5 nm; the average length of the carbon nanotubes is 15-20 μm.
[0047] In the present application, adding modified fillers to the waterproof coating of the swimming cap can greatly improve the waterproof, antistatic and dirt-resistant properties of the swimming cap, while maintaining good mechanical properties and having good comfort of the swimming cap. First, the modified filler can form a composite structure of strip carbon nanotubes, particle zinc oxide and framework structure. The formation of this structure can greatly increase the overall support strength of the composite particles mainly composed of framework structure and carbon nanotubes, and through the modification of surface groups, it greatly strengthens the connection force between it and the organic polysiloxane system, so it can show good mechanical support under the action of external force; secondly, the composite structure formed by it can form a particle surface with extremely low surface energy, and when it acts on the coating surface, it can also greatly enhance the surface roughness to form a complex surface continuous protrusion structure. The existence of this structure greatly increases the difficulty and time for water molecules to form a hydrophilic hydration layer on the surface of the swimming cap coating, thereby greatly improving the waterproofness; finally, the formed composite particle structure can enhance the light energy absorption efficiency of zinc oxide particles under light, increase the number of carriers generated, and greatly reduce the bandgap distance through the passage effect, so that it can effectively decompose surface organic dirt when used outdoors, thereby greatly improving the dirt resistance.
[0048] As a preferred solution, the surfactant is cetearyl alcohol polyoxyethylene ether.
[0049] As a preferred solution, the auxiliary agent is a composition of epoxy block polymer and pullulan.
[0050] As a preferred solution, the mass ratio of the epoxy block polymer to the pullulan is (1.8-2.5): (5.5-6.5).
[0051] As a preferred solution, the weight average molecular weight of the epoxy block polymer is 2000~6000Da.
[0052] As a preferred solution, the weight average molecular weight of the epoxy block polymer is 4000~5000 Da.
[0053] As a preferred solution, the branch content of the amylopectin is ≥75%.
[0054] The composition of epoxy block polymer and amylopectin added in the present application can greatly improve the mechanical strength of the swimming cap while ensuring its antistatic performance. The combination of epoxy block polymer and amylopectin after addition can form a good connection three-dimensional network structure in the organopolysiloxane system, and through the multi-branched guiding effect of amylopectin, the dispersion effect of the modified filler is guaranteed in the system, avoiding excessive aggregation due to the action of the surface active groups, and then forming a good continuous dispersion effect of the internal modified filler, thereby providing a good external surface dissipation path for the charge, avoiding a large amount of charge accumulation; when the relative content of amylopectin is low and the weight average molecular weight of the epoxy block polymer is high, the formation of the continuous dispersion system of the modified filler is suppressed, thereby significantly reducing the surface antistatic effect.
[0055] As a preferred solution, the colorant is at least one of phthalocyanine blue, phthalocyanine green, iron oxide, ferrous oxide, titanium dioxide, and carbon black.
[0056] The second aspect of the present application provides a method for preparing the above-mentioned swimming cap containing the silicone waterproof coating, and the preparation method comprises the following steps: S1: respectively mix the raw materials of the colloid layer and the silicone waterproof coating evenly and set them aside; S2: prepare a cut base layer, apply the colloid layer raw material on the surface of the base layer, and form a colloid layer after heating and curing; S3: apply the silicone waterproof coating on the surface of the colloid layer, and form the silicone waterproof coating after heating and curing to obtain the prepared cloth leather; S4: add the prepared cloth leather to the swimming cap molding mold, and perform trimming and seam filling after molding to obtain the prepared cloth leather.
[0057] The beneficial effects of this application are: 1. The present application provides a swimming cap containing a silicone waterproof coating, which has excellent mechanical / mechanical properties while ensuring good waterproof, antistatic and dirt-resistant properties, greatly improving the quality and service life of existing swimming caps, and has very excellent market and application prospects.
[0058] 2. A swimming cap containing a silicone waterproof coating provided in the present application, wherein adding a modified filler to the waterproof coating of the swimming cap can greatly improve the waterproof, antistatic and dirt-resistant properties of the swimming cap; the modified filler can form a composite structure of strip carbon nanotubes, particle zinc oxide and a framework structure, the formation of which can greatly increase the overall supporting strength of the composite particles mainly composed of the framework structure and the carbon nanotubes, and through the modification of the surface groups, greatly enhance the connection force between the composite particles and the organic polysiloxane system; the formed composite structure can form a particle surface with extremely low surface energy, and when acting on the coating surface, it can also greatly enhance the surface roughness, forming a complex surface continuous protrusion structure, the existence of which greatly increases the difficulty and time for water molecules to form a hydrophilic hydration layer on the surface of the swimming cap coating, thereby greatly improving the waterproofness.
[0059] 3. A swimming cap containing a silicone waterproof coating provided in the present application has a composite particle structure formed by the added modified filler, which can enhance the light energy absorption efficiency of zinc oxide particles under light, increase the number of carriers generated, and greatly reduce the bandgap distance through the passage effect, thereby effectively decomposing organic dirt on the surface when used outdoors, thereby greatly improving the dirt resistance.
[0060] 4. A swimming cap containing a silicone waterproof coating provided in the present application, wherein the added composition of epoxy block polymer and amylopectin can greatly improve the mechanical strength of the swimming cap while ensuring its antistatic performance; the combination of the added epoxy block polymer and amylopectin can form a well-connected three-dimensional network structure in the organopolysiloxane system, and through the multi-branch guiding effect of amylopectin, the dispersion effect of the modified filler is guaranteed in the system, avoiding excessive aggregation caused by the action of surfactant groups, thereby forming a good continuous dispersion effect of the internal modified filler, thereby providing a good external surface dissipation path for the charge, avoiding a large amount of charge accumulation.
[0061] 5. A swimming cap containing a silicone waterproof coating provided in the present application can greatly reduce the penetration effect of water molecules and active molecules into the coating through the combined action of compounded additives and modified fillers, reduce the collision probability and contact frequency of active molecules inside the coating, and thus greatly reduce the probability of adverse chemical reactions in the coating system during long-term use, thereby having excellent aging resistance and greatly improving the performance of the swimming cap. DETAILED DESCRIPTION
[0062] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0063] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0064] Example 1 Embodiment 1 provides a swimming cap containing a silicone waterproof coating in a first aspect, and its structure includes: a base layer, a colloid layer located on the surface of the base layer, and the silicone waterproof coating located on the surface of the colloid layer.
[0065] The thickness of the base layer is 0.25 mm; the thickness of the colloid layer is 0.05 mm; the thickness of the silicone waterproof coating is 0.15 mm; and the total thickness of the swimming cap is 0.45 mm.
[0066] The base layer is polyester fabric, which is purchased from the polyester fabric products sold by Guangzhou Sibo Chemical Technology Co., Ltd.
[0067] The raw materials of the colloidal layer, by mass, include: 90 parts of organic polysiloxane I, 6.5 parts of hydrogenated polysiloxane I, 25 parts of modified resin I, 1.2 parts of catalyst, 24 parts of filler, 4.8 parts of dispersant, and 8.5 parts of flame retardant.
[0068] Organic polysiloxane I is a composition of polydimethylsiloxane and epoxy-modified polysiloxane, with a mass ratio of 5.2:1.8. The viscosity of epoxy-modified polysiloxane is 1800cp, the test temperature is 25°C, and it is purchased from the sh-023 model product sold by Hubei Longsheng Sihai New Materials Co., Ltd. The viscosity of polydimethylsiloxane is 7500cp, the test temperature is 25°C, and it is purchased from the corresponding viscosity product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd.
[0069] Hydrogenated polysiloxane I is hydrogenated end-capped polydimethylsiloxane with a hydrogen content of 0.75 wt%, which was purchased from Jiangxi Xinjiayi New Materials Co., Ltd. to sell products with corresponding hydrogen content.
[0070] Modified resin I is vinyl MTQ resin, purchased from RIP Corporation, a PPA400 model vinyl MTQ resin product, with a vinyl content of 2.5 wt%.
[0071] The catalyst is CAT-PL-56 platinum catalyst.
[0072] The filler is sericite powder, and the average particle size of the sericite powder is 0.15 μm.
[0073] The dispersant is polyethylene glycol 800. The flame retardant is triphenyl phosphate.
[0074] The raw materials of the organosilicon waterproof coating, measured in parts by mass, include: 110 parts of organopolysiloxane ⅠⅠ, 16 parts of hydrogenated polysiloxane ⅠⅠ, 28 parts of modified resin ⅠⅠ, 2.2 parts of cross-linking agent, 1.2 parts of catalyst, 28 parts of modified filler, 8.5 parts of surfactant, 12.5 parts of auxiliary agent, and 6.5 parts of colorant.
[0075] The organopolysiloxane ⅠⅠ is a composition of high-viscosity vinyl polydimethylsiloxane and low-viscosity vinyl polydimethylsiloxane, and the mass ratio of the two is 4.4:2.5.
[0076] The viscosity of high viscosity vinyl polydimethylsiloxane is 12000cp, the test temperature is 25°C, and the corresponding viscosity product is purchased from Shenzhen Xinyongsheng New Materials Co., Ltd.; the viscosity of low viscosity vinyl polydimethylsiloxane is 5000cp, the test temperature is 25°C, and the corresponding viscosity product is purchased from Hubei Chengfeng Chemical Co., Ltd.
[0077] Hydrogenated polysiloxane ⅠⅠ is polymethyl hydrogen siloxane with a hydrogen content of 1.6 wt %, which was purchased from Hubei Xinghengye Technology Co., Ltd.
[0078] The modified resin ⅠⅠ is a composition of vinyl MTQ resin and methyl vinyl MQ resin, and the mass ratio of the two is 1.2:3.8.
[0079] The catalyst is CAT-PL-56 platinum catalyst.
[0080] Vinyl MTQ resin was purchased from PPA400 model vinyl MTQ resin product sold by Ruipu Company, with a vinyl content of 2.5wt%; methyl vinyl MQ resin was purchased from methyl vinyl MQ resin product sold by Jiangxi Xinjiayi New Materials Co., Ltd., with a vinyl content of 1.2wt%.
[0081] The crosslinking agent is dicumyl peroxide.
[0082] The preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.2 parts of carbon nanotubes and 0.8 parts of zinc oxide are mixed and added to 80 parts of deionized water, the temperature is raised to 60°C, 1.1 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane are added, the reaction is stirred at a speed of 100 r / min for 2.5 hours, and after completion, centrifugal precipitation and washing are performed to obtain pretreated composite particles; S2: 2.25 parts of the pretreated composite particles are added to 60 parts of deionized water and mixed evenly with 1.76 parts of a methanol solution of zinc acetate (a total of 20 parts), the temperature is raised to 60°C, 1.1 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane are added, the reaction is stirred at a speed of 100 r / min for 2.5 hours, and the pretreated composite particles are centrifuged and precipitated after completion to obtain pretreated composite particles; S2: 2.25 parts of the pretreated composite particles are added to 60 parts of deionized water and mixed evenly with 1.76 parts of a methanol solution of zinc acetate (a total of 20 parts), the temperature is raised to 60°C, 1.1 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane are added, the reaction is stirred at a speed of 100 r / min for 2.5 hours, and the pretreated composite particles are centrifuged and precipitated after washing to obtain pretreated composite particles. Heat to 55°C, keep warm for 35 minutes, then raise the temperature to 65°C, and drop 1.1 parts of dimethylimidazole methanol solution (20 parts in total), the dropping time is 1 hour; S3: after the dropwise addition is completed, cool to 50°C, heat with 250W power for ultrasonic reaction for 3.5 hours, after the reaction is completed, add ammonia water to the obtained product to adjust the pH to 9, then add 0.42 parts of ethyl orthosilicate ethanol solution (10 parts in total), keep warm at 60°C and stir to react for 1.2 hours, after the reaction is completed, wait until the product in the solution is completely precipitated, filter and wash the product solution, and vacuum dry it to obtain.
[0083] The average diameter of the carbon nanotubes is 2 nm; the average length of the carbon nanotubes is 16.5 μm, and the carbon nanotubes are purchased from products of corresponding sizes sold by Zhongke Leiming (Beijing) Technology Co., Ltd.
[0084] The surfactant is cetearyl alcohol polyoxyethylene ether, which was purchased from the cetearyl alcohol ether A-50 product sold by Hai'an Petrochemical Plant in Jiangsu Province.
[0085] The composite material comprises an auxiliary epoxy block polymer and amylopectin, and the mass ratio of the two is 2:6.
[0086] The weight average molecular weight of the epoxy block polymer was 4600 Da, and it was purchased from BASF as a L85 product.
[0087] The branched starch was purchased from Shandong West Asia Chemical Co., Ltd., with a branched content of 75.5%.
[0088] The colorant is phthalocyanine blue.
[0089] The second aspect of the present embodiment provides a method for preparing the above-mentioned swimming cap containing the silicone waterproof coating, and the preparation method comprises the following steps: S1: respectively mix the raw materials of the colloid layer and the silicone waterproof coating evenly and set them aside; S2: prepare a cut base layer, apply the colloid layer raw material on the surface of the base layer, and heat and cure it at 100°C to form a colloid layer; S3: apply the silicone waterproof coating on the surface of the colloid layer, and heat and cure it at 120°C to form the silicone waterproof coating, so as to obtain the prepared cloth leather; S4: add the prepared cloth leather to the swimming cap molding mold, and perform trimming and seam filling treatments after molding to obtain the prepared cloth leather.
[0090] Example 2 Embodiment 2 provides a swimming cap containing a silicone waterproof coating in the first aspect, and its structure includes: a base layer, a colloid layer located on the surface of the base layer, and the silicone waterproof coating located on the surface of the colloid layer.
[0091] The thickness of the base layer is 0.25 mm; the thickness of the colloid layer is 0.05 mm; the thickness of the silicone waterproof coating is 0.15 mm; and the total thickness of the swimming cap is 0.45 mm.
[0092] The base layer is polyester fabric, which is purchased from the polyester fabric products sold by Guangzhou Sibo Chemical Technology Co., Ltd.
[0093] The raw materials of the colloidal layer, by mass, include: 85 parts of organic polysiloxane I, 7.5 parts of hydrogenated polysiloxane I, 24 parts of modified resin I, 1.2 parts of catalyst, 24 parts of filler, 4.8 parts of dispersant, and 8.5 parts of flame retardant.
[0094] Organic polysiloxane I is a composition of polydimethylsiloxane and epoxy-modified polysiloxane, with a mass ratio of 5.5:1.6. The viscosity of epoxy-modified polysiloxane is 1800cp, the test temperature is 25°C, and it is purchased from the sh-023 model product sold by Hubei Longsheng Sihai New Materials Co., Ltd. The viscosity of polydimethylsiloxane is 7500cp, the test temperature is 25°C, and it is purchased from the corresponding viscosity product sold by Shanghai Hongzhuang Chemical Technology Co., Ltd.
[0095] Hydrogenated polysiloxane I is hydrogenated end-capped polydimethylsiloxane with a hydrogen content of 0.75 wt%, which was purchased from Jiangxi Xinjiayi New Materials Co., Ltd. to sell products with corresponding hydrogen content.
[0096] Modified resin I is vinyl MTQ resin, purchased from RIP Corporation, a PPA400 model vinyl MTQ resin product, with a vinyl content of 2.5 wt%.
[0097] The catalyst is CAT-PL-56 platinum catalyst.
[0098] The filler is sericite powder, and the average particle size of the sericite powder is 0.15 μm.
[0099] The dispersant is polyethylene glycol 800. The flame retardant is triphenyl phosphate.
[0100] The raw materials of the organic silicone waterproof coating, measured in parts by mass, include: 100 parts of organic polysiloxane ⅠⅠ, 18.5 parts of hydrogenated polysiloxane ⅠⅠ, 25 parts of modified resin ⅠⅠ, 2.2 parts of cross-linking agent, 1.2 parts of catalyst, 26.5 parts of modified filler, 8.5 parts of surfactant, 12.5 parts of auxiliary agent, and 6.5 parts of colorant.
[0101] The organopolysiloxane ⅠⅠ is a composition of high viscosity vinyl polydimethylsiloxane and low viscosity vinyl polydimethylsiloxane, and the mass ratio of the two is 5:2.
[0102] The viscosity of high viscosity vinyl polydimethylsiloxane is 12000cp, the test temperature is 25°C, and the corresponding viscosity product is purchased from Shenzhen Xinyongsheng New Materials Co., Ltd.; the viscosity of low viscosity vinyl polydimethylsiloxane is 5000cp, the test temperature is 25°C, and the corresponding viscosity product is purchased from Hubei Chengfeng Chemical Co., Ltd.
[0103] Hydrogenated polysiloxane ⅠⅠ is polymethyl hydrogen siloxane with a hydrogen content of 1.6 wt %, which was purchased from Hubei Xinghengye Technology Co., Ltd.
[0104] The modified resin ⅠⅠ is a composition of vinyl MTQ resin and methyl vinyl MQ resin, and the mass ratio of the two is 1.5:3.5.
[0105] The catalyst is CAT-PL-56 platinum catalyst.
[0106] Vinyl MTQ resin was purchased from PPA400 model vinyl MTQ resin product sold by Ruipu Company, with a vinyl content of 2.5wt%; methyl vinyl MQ resin was purchased from methyl vinyl MQ resin product sold by Jiangxi Xinjiayi New Materials Co., Ltd., with a vinyl content of 1.2wt%.
[0107] The crosslinking agent is dicumyl peroxide.
[0108] The preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.2 parts of carbon nanotubes and 0.8 parts of zinc oxide are mixed and added to 80 parts of deionized water, the temperature is raised to 60°C, 1.1 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane are added, the reaction is stirred at a speed of 100 r / min for 2.5 hours, and after completion, centrifugal precipitation and washing are performed to obtain pretreated composite particles; S2: 2.25 parts of the pretreated composite particles are added to 60 parts of deionized water and mixed evenly with 1.76 parts of a methanol solution of zinc acetate (a total of 20 parts), the temperature is raised to 60°C, 1.1 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane are added, the reaction is stirred at a speed of 100 r / min for 2.5 hours, and the pretreated composite particles are centrifuged and precipitated after completion to obtain pretreated composite particles; S2: 2.25 parts of the pretreated composite particles are added to 60 parts of deionized water and mixed evenly with 1.76 parts of a methanol solution of zinc acetate (a total of 20 parts), the temperature is raised to 60°C, 1.1 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane are added, the reaction is stirred at a speed of 100 r / min for 2.5 hours, and the pretreated composite particles are centrifuged and precipitated after washing to obtain pretreated composite particles. Heat to 55°C, keep warm for 35 minutes, then raise the temperature to 65°C, and drop 1.1 parts of dimethylimidazole methanol solution (20 parts in total), the dropping time is 1 hour; S3: after the dropwise addition is completed, cool to 50°C, heat with 250W power for ultrasonic reaction for 3.5 hours, after the reaction is completed, add ammonia water to the obtained product to adjust the pH to 9, then add 0.42 parts of ethyl orthosilicate ethanol solution (10 parts in total), keep warm at 60°C and stir to react for 1.2 hours, after the reaction is completed, wait until the product in the solution is completely precipitated, filter and wash the product solution, and vacuum dry it to obtain.
[0109] The average diameter of the carbon nanotubes is 2 nm; the average length of the carbon nanotubes is 16.5 μm, and the carbon nanotubes are purchased from products of corresponding sizes sold by Zhongke Leiming (Beijing) Technology Co., Ltd.
[0110] The surfactant is cetearyl alcohol polyoxyethylene ether, which was purchased from the cetearyl alcohol ether A-50 product sold by Hai'an Petrochemical Plant in Jiangsu Province.
[0111] The composite material comprises an auxiliary epoxy block polymer and amylopectin, and the mass ratio of the two is 2:6.
[0112] The weight average molecular weight of the epoxy block polymer was 4600 Da, and it was purchased from BASF as a L85 product.
[0113] The branched starch was purchased from Shandong West Asia Chemical Co., Ltd., with a branched content of 75.5%.
[0114] The colorant is phthalocyanine blue.
[0115] The second aspect of the present embodiment provides a method for preparing the above-mentioned swimming cap containing the silicone waterproof coating, and the preparation method comprises the following steps: S1: respectively mix the raw materials of the colloid layer and the silicone waterproof coating evenly and set them aside; S2: prepare a cut base layer, apply the colloid layer raw material on the surface of the base layer, and heat and cure it at 100°C to form a colloid layer; S3: apply the silicone waterproof coating on the surface of the colloid layer, and heat and cure it at 120°C to form the silicone waterproof coating, so as to obtain the prepared cloth leather; S4: add the prepared cloth leather to the swimming cap molding mold, and perform trimming and seam filling treatments after molding to obtain the prepared cloth leather.
[0116] Comparative Example 1 The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being that the raw materials of the silicone waterproof coating, in parts by mass, include: 110 parts of organopolysiloxane ⅠⅠ, 16 parts of hydrogenated polysiloxane ⅠⅠ, 28 parts of modified resin ⅠⅠ, 2.2 parts of cross-linking agent, 1.2 parts of catalyst, 12 parts of modified filler, 8.5 parts of surfactant, 6.5 parts of auxiliary agent, and 6.5 parts of colorant.
[0117] Comparative Example 2 The specific implementation of this comparative example is basically the same as that of Example 1, except that the organopolysiloxane ⅠⅠ is a composition of high-viscosity vinyl polydimethylsiloxane and low-viscosity vinyl polydimethylsiloxane, and the mass ratio of the two is 8:1.
[0118] Comparative Example 3 The specific implementation of this comparative example is basically the same as that of Example 1, except that the modified resin ⅠⅠ is a composition of vinyl MTQ resin and methyl vinyl MQ resin, and the mass ratio of the two is 0.5:6.
[0119] Comparative Example 4 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: 5.5 parts of carbon nanotubes and 0.2 parts of zinc oxide are mixed and added to 120 parts of deionized water, the temperature is raised to 60°C, 0.6 parts of succinic anhydride and 0.22 parts of 3-aminopropyltriethoxysilane are added, the reaction is stirred at a speed of 100 r / min for 2.5 hours, and after completion, the centrifugal precipitation is washed to obtain pretreated composite particles; S2: 2.25 parts of the pretreated composite particles are added to 60 parts of deionized water and 1.76 parts of zinc acetate in a mixture of methyl The alcohol solution (20 parts in total) was mixed evenly, heated to 55°C, kept warm for 35 minutes, then heated to 65°C, and 1.1 parts of dimethylimidazole methanol solution (20 parts in total) were added dropwise, and the addition time was 1 hour; S3: After the addition was completed, the temperature was lowered to 50°C, and ultrasonic heating was performed at a power of 250W for 3.5 hours. After the reaction was completed, ammonia water was added to the obtained product to adjust the pH to 9, and then 0.42 parts of ethyl orthosilicate ethanol solution (10 parts in total) was added, and the reaction was stirred at 60°C for 1.2 hours. After the reaction was completed, the product in the solution was completely precipitated, the product solution was filtered and washed, and vacuum dried to obtain the product.
[0120] Comparative Example 5 The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler comprises the following steps, calculated by mass: S1: 3.2 parts of carbon nanotubes and 0.8 parts of zinc oxide are mixed and added to 80 parts of deionized water, the temperature is raised to 60°C, 1.1 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane are added, the reaction is stirred at a speed of 100 r / min for 2.5 hours, and after completion, the centrifugal precipitation is washed to obtain pretreated composite particles; S2: 4.5 parts of the pretreated composite particles are added to 80 parts of deionized water and 0.85 parts of zinc acetate in methanol. The mixture was mixed evenly, heated to 55°C, kept warm for 35 minutes, then heated to 65°C, and 0.62 parts of a methanol solution of dimethylimidazole (15 parts) were added dropwise, and the addition time was 1 hour; S3: After the addition was completed, the temperature was lowered to 50°C, and ultrasonic heating was performed at a power of 250W for 3.5 hours. After the reaction was completed, ammonia water was added to the obtained product to adjust the pH to 9, and then 0.25 parts of an ethanol solution of tetraethyl orthosilicate (10 parts) were added, and the mixture was stirred at 60°C for 1.2 hours. After the reaction was completed, the product in the solution was completely precipitated, and the product solution was filtered, washed, and vacuum dried to obtain the product.
[0121] Comparative Example 6 The specific implementation of this comparative example is basically the same as that of Example 1, except that the mass ratio of the epoxy block polymer to the pullulan is 0.5:7.5.
[0122] Comparative Example 7 The specific implementation of this comparative example is basically the same as that of Example 1, except that the weight average molecular weight of the epoxy block polymer is 10,800 Da, and it is purchased from BASF as a L88 product.
[0123] Comparative Example 8 The specific implementation of this comparative example is basically the same as that of Example 1, except that the hydrogen content of the polymethylhydrogensiloxane is 0.6 wt %, which is a product with a corresponding hydrogen content purchased from Hubei Xinghengye Technology Co., Ltd.
[0124] Performance Evaluation Mechanical properties: The swimming caps prepared in the embodiments and comparative examples were subjected to mechanical property tests, with the fracture of the surface silicone waterproof coating as the test node. The elongation at break of the coating that the swimming cap can withstand at the test node was measured using a universal tensile machine. The test values were averaged over 10 tests and recorded in Table 1.
[0125] Waterproofness: The waterproof coating on the surface of the swimming cap obtained in the embodiment and the comparative example was subjected to a sessile drop method water contact angle test. The test drop size was 2.5 μL and the test time was 15 s. The corresponding water contact angle was measured. The test value was the average of 10 tests and recorded in Table 1.
[0126] Aging resistance: The swimming caps prepared in the embodiments and comparative examples were cut into 2 cm × 2 cm samples and placed in a constant temperature and humidity chamber at 65°C and 75% relative humidity for 3 months. After 3 months, the surface was observed for cracking, yellowing, and blistering. If so, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group. The aging resistance qualified rate (%) = number of qualified samples / 50 × 100%. The results are recorded in Table 1.
[0127] Table 1 Performance test results
[0128] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious performance advantages over comparative examples 1 to 8 in terms of mechanical properties, waterproof properties and aging resistance. This is mainly due to the combined addition of modified fillers and compounding additives in the waterproof coating of the present application. Comparative examples 1 to 8 did not adopt the correct technical solution, resulting in obvious gaps in the corresponding performance tests. This further proves the necessity of the technical solution defined in the present application for technical effects and solving technical problems.
Claims
1. A swimming cap with a silicone waterproof coating, characterized in that: A swimming cap containing an organic silicon waterproof coating, the structure of which comprises: a base layer, a colloid layer located on the surface of the base layer, and an organic silicon waterproof coating located on the surface of the colloid layer; The total thickness of the swimming cap is 0.3-0.6 mm; The thickness of the base layer is 0.2-0.4 mm; The thickness of the colloid layer is 0.04-0.08 mm; The thickness of the silicone waterproof coating is 0.1-0.2 mm; The base layer is any one of polyester, aramid, spandex or a blended fabric of two of them; The raw materials of the colloidal layer include, by mass, 80-100 parts of organopolysiloxane I, 5-10 parts of hydrogenated polysiloxane I, 20-35 parts of modified resin I, 0.5-3 parts of catalyst, 20-25 parts of filler, 1-6 parts of dispersant, and 4-10 parts of flame retardant; The organopolysiloxane I is a composition of polydimethylsiloxane and epoxy-modified polysiloxane; the mass ratio of the polydimethylsiloxane to the epoxy-modified polysiloxane is (4-6): (1.5-2); The viscosity of the epoxy-modified polysiloxane is 1000-2500 cp, and the test temperature is 25°C; The hydrogenated polysiloxane I is hydrogenated end-capped polydimethylsiloxane; the hydrogen content of the hydrogenated polysiloxane I is 0.5-1 wt%; The modified resin I is vinyl MTQ resin; The raw materials of the organic silicon waterproof coating include, by weight: 100-120 parts of organic polysiloxane ⅠⅠ, 10-20 parts of hydrogenated polysiloxane ⅠⅠ, 20-35 parts of modified resin ⅠⅠ, 0.5-3 parts of cross-linking agent, 0.5-2 parts of catalyst, 20-30 parts of modified filler, 5-10 parts of surfactant, 10-15 parts of auxiliary agent, and 4-8 parts of colorant; The organopolysiloxane ⅠⅠ is a composition of high viscosity vinyl polydimethylsiloxane and low viscosity vinyl polydimethylsiloxane; the mass ratio of the high viscosity vinyl polydimethylsiloxane to the low viscosity vinyl polydimethylsiloxane is (3.5-5): (2-2.5); The hydrogenated polysiloxane ⅠⅠ is polymethyl hydrogen siloxane; the hydrogen content of the polymethyl hydrogen siloxane is 1.2-1.6wt%.
2. The swimming cap with silicone waterproof coating according to claim 1, characterized in that: The mass ratio of the organopolysiloxane I to the modified resin I is (8.5-9.5):(2.4-2.6).
3. The swimming cap with silicone waterproof coating according to claim 2, characterized in that: The catalyst is any one of platinum catalysts.
4. The swimming cap with silicone waterproof coating according to claim 3, characterized in that: The filler is at least one of talcum powder, white carbon black, bentonite and sericite powder.
5. The swimming cap with silicone waterproof coating according to claim 4, characterized in that: The dispersant is at least one of alkyl glycoside, lauryl alcohol polyoxyethylene ether, povidone, polyethylene glycol and betaine.
6. The swimming cap with silicone waterproof coating according to claim 5, characterized in that: The flame retardant is at least one of aluminum hydroxide, magnesium hydroxide, triphenyl phosphate, zinc borate, MCA, and MA.
7. The swimming cap with silicone waterproof coating according to claim 6, characterized in that: The viscosity of the high-viscosity vinyl polydimethylsiloxane is 10000-14000 cp, and the test temperature is 25°C; the viscosity of the low-viscosity vinyl polydimethylsiloxane is 4000-6000 cp, and the test temperature is 25°C.
8. The swimming cap with silicone waterproof coating according to claim 7, characterized in that: The modified resin II is a composition of vinyl MTQ resin and methyl vinyl MQ resin; the mass ratio of the vinyl MTQ resin to the methyl vinyl MQ resin is (1-1.5): (3.5-4).
9. The swimming cap with silicone waterproof coating according to claim 8, characterized in that: Preparation method of the modified filler The following steps are involved: S1: Mix carbon nanotubes and zinc oxide and add them into deionized water, raise the temperature to 60-65°C, add succinic anhydride and silane coupling agent, stir at 80-120 r / min for 2-3 hours, centrifuge and wash after completion to obtain pretreated composite particles; S2: Add deionized water to the pretreated composite particles and mix them evenly with the methanol solution of zinc acetate, raise the temperature to 50-55°C, keep the temperature for 30-40 minutes, then raise the temperature to 65-70°C, and drop the methanol solution of dimethylimidazole for 1-1.5 hours; S3: After the addition is completed, the temperature is lowered to 45-50°C, and ultrasonic heating is performed at a power of 200-300W for a reaction of 3-3.5h. After the reaction is completed, ammonia water is added to the obtained product to adjust the pH to 8.5-9.5, and then an ethanol solution of tetraethyl orthosilicate is added. The mixture is stirred at 55-60°C for a reaction of 1-1.5h. After the reaction is completed, the product in the solution is completely precipitated, and the product solution is filtered, washed, and vacuum dried to obtain the product.
10. A method for preparing a swimming cap containing a silicone waterproof coating according to any one of claims 1 to 9, characterized in that: Preparation method The following steps are involved: S1: respectively mix the raw materials of the colloid layer and the silicone waterproof coating evenly and set them aside; S2: prepare the cut base layer, apply the raw materials of the colloid layer on the surface of the base layer, and heat and cure to form a colloid layer; S3: apply the silicone waterproof coating on the surface of the colloid layer, and heat and cure to form the silicone waterproof coating to obtain the prepared cloth leather; S4: add the prepared cloth leather to the swimming cap molding mold, and perform trimming and seam filling after molding to obtain the prepared cloth leather.
